A Conceptual Framework for Reverse Logistics Performance and Innovation - Ramesh, Ganesh Kumar; J R, Ashlin Nimo (International Journal of Supply Chain Management, 2020)
Green Supply Chain Management has been receiving a lot of attention in recent times. Attention on Reverse Logistics (RL) area has also been steadily growing. Reverse Logistics involves reduce-reuse-recycle as well as redesign, remanufacture, etc. It is a closed loop of the Supply Chain for value creation. Carter and Ellram (1998) discuss that Reverse Logistics can result in savings for an organization. Daugherty, Richey, Genchev, and Chen (2005) analyze where the resources in Reverse Logistics could be committed to achieve good Reverse Logistics Performance. The Automotive after-market in India is also in its nascent stages and has a huge scope for growth. Thus, a study in this area is definitely warranted. This paper gives a Conceptual framework for the RL Performance and Innovation in Automotive after-market with an emerging economy backdrop. The authors of this paper find fewer papers in these areas and this paper aims to fill this gap.